The emerging role of CCN6 in breast cancer invasion - Lorenzatti, Guadalupe (Cellscience, 2009)
The CCN family of matricellular proteins is essential for cell communication and mediation of epithelial stromal cross-talks with roles in development and cancer. In particular, loss of CCN6 messenger RNA expression has been recognized in highly aggressive breast cancers, especially in inflammatory breast cancer and breast cancers with axillary lymph node metastasis. Recent findings can better explain the relevance of CCN6’s reduced expression on human invasive breast carcinomas. CCN6 has been shown to play a role in the process of epithelial to mesenchymal transition (EMT), which converts epithelial cells into migratory mesenchymal-like cells with invasive abilities. Although the mechanism by which CCN6 promotes EMT and invasion has not been fully elucidated, current data suggest that it involves the recruitment of the transcriptional regulators Snai1 and ZEB1 to the E-cadherin promoter.